Analysis of power from palm oil solid waste for biomass power plants: A case study in Aceh Province. (August 2020) - Mahidin,; Saifullah,; Erdiwansyah,; Hamdani,; Hisbullah,; Hayati, A.P.; Zhafran, M.; Sidiq, M.A.; Rinaldi, A.; Fitria, B.; Tarisma, R.; Bindar, Y.
Abstract: Nowadays, the solid waste produced from palm oil has become one of the essential oils in the world in general and especially in Indonesia. Biomass waste is processed through substantial quantities of palm oil extraction. With the reduction in fossil fuels in recent years, it has had an impact on the deterioration of electricity supply at the National and International levels. Biomass is a renewable energy that can replace conventional energy. Besides, power generation from biomass is environmentally friendly and sustainable. This simulation was conducted to analyze the maximum power from the burning of oil palm biomass for the electricity generation. The novelty of the article is the performance and behavior of palm oil biomass-based co-fuel in the power generation process. The biomass wastes used in this simulation include OPF, EFB, PKS, and OPM. The results of this simulation indicate that the maximum power produced with OPF can produce 49.54 MW with variations in the flow rate of biomass at 8 kg/s. While at the time of recycling up to 100% OPM biomass produces 61.05 MW higher than OPF, EFB and PKS. Meanwhile, the OPF-PKS mixed biomass can produce 106.15 MW of power plants when the airflow rate reaches 171 kg/s. The overall results of the simulation for the analysis of the maximum power that can be used as a power station show suitability and can apply in rural/remote areas. Besides, the availability of oil palm biomass in Aceh Province is also sufficient to overcome electricity shortages and reduce dependence on conventional energy. Graphical abstract: Image 1 Highlights: Analysis carried out with ASPEN PLUS using four types of oil palm biomass. Single oil palm biomass can produce 61.05 MW with an 8 kg/s biomass flow rate. The potential for palm oil biomass fuel production is renewable and sustainable energy. Biomass blend can produce electricity up 106.15 MW with a flow rate of 171 kg/s. This simulation determines design electricity generation by utilize oil palm biomass.